Insights into the Photothermal Hydrogen Production from Glycerol Aqueous Solutions over Noble Metal‐Free Ti@TiO2 Core–Shell Nanoparticles. (13th August 2018) - Nikitenko, Sergey I.; Chave, Tony; Goff, Xavier Le
Abstract: Photocatalytic production of hydrogen from renewable sources with platinum group metal‐free catalysts is of great importance for environmentally friendly energetics. Herein, Ti@TiO2 core–shell nanoparticles prepared by sonohydrothermal treatment of titanium metal nanoparticles are examined for hydrogen generation from aqueous glycerol solutions under vis/NIR light irradiation. It is shown that photocatalytic reforming of glycerol in the presence of Ti@TiO2 exhibits strong photothermal effect allowing more efficient use of solar energy. Apparent activation energy equal to E act = 27 ± 2 kJ mol −1 indicates that the thermal effect is related to the diffusion of reaction intermediates at catalyst surface rather than to the activation of chemical bonds. The photoexcitation mechanism of Ti@TiO2 particles involves interband transitions in nonplasmonic Ti metal core followed by nonradiative Landau damping. Effective electron–hole separation between Ti core and nanocrystalline TiO2 anatase shell in Ti@TiO2 nanoparticles is confirmed by photoluminescence spectroscopy. In studied system, photothermal hydrogen production is not accompanied by CO2 emission indicating that glycerol is oxidized to glyceric acid without further decarboxylation. Abstract : Ti@TiO2 core–shell nanoparticles exhibit strong photothermal effect in the process of glycerol reforming allowing more efficient use of solar energy. The photoexcitation mechanism of Ti@TiO2 particles involves interband transitions in nonplasmonic Ti metal core followed by nonradiative Landau damping. Effective electron–hole separation between Ti core and nanocrystalline TiO2 shell was confirmed by photoluminescence spectroscopy.